Infective endocarditis with embolic complications caused by Abiotrophia defective. A case report. - Aslanides, Iris; Tuerlinckx, David; Barrea, Catherine; Chatzis, Olga (Belgian Journal of Paediatrics, 2023)
We describe the case of Abiotrophia defectiva infective endocarditis in a 13-year old boy with underlying cardiac abnormalities. Our patient presented with atypical symptoms, leading to delayed diagnosis and several complications. After antibiotical treatment, surgical intervention was indicated. Infective endocarditis (IE) caused by nutritionally variant streptococci in pediatric population is rare. These fastidious microorganisms are known to be responsible for complicated IE. This case report illustrates the atypical presentations of IE. It also reminds us that IE should rapidly be raised in patients with predisposing factors, such as structural congenital heart disease, and emphasizes the importance of blood cultures.